2021
DOI: 10.18632/aging.202970
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy effectively alleviates D-galactose-induced-age-related cardiac dysfunction via attenuating mitochondrial dysfunction in pre-diabetic rats

Abstract: Currently, the prevalence of obesity in aging populations is fast growing worldwide. Aging induced by D-galactose (D-gal) is proven to cause the worsening of cardiac dysfunction in pre-diabetic rats via deteriorating cardiac mitochondrial function. Hyperbaric oxygen therapy (HBOT) has been shown to attenuate D-gal-induced cognitive deterioration through decreased inflammation and apoptosis. We tested the hypothesis that HBOT alleviates D-gal induced cardiac dysfunction via improving mitochondrial function in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…The myocardium of elderly diabetic patients is particularly vulnerable to the adverse effects of local and systemic factors caused by diabetes. In pre-diabetic rats after D-gal-induced aging, HBOT ameliorated the aggravation of cardiac dysfunctions [ 98 ], consistent with a previous clinical trial involving elderly diabetic patients, in which HBOT resulted in improved myocardial diastolic function [ 191 ]. Researchers also examined the effects of HBOT on myocardial function during normal aging.…”
Section: Therapeutic Implications Of Hbot In Aging Interventionsupporting
confidence: 79%
See 4 more Smart Citations
“…The myocardium of elderly diabetic patients is particularly vulnerable to the adverse effects of local and systemic factors caused by diabetes. In pre-diabetic rats after D-gal-induced aging, HBOT ameliorated the aggravation of cardiac dysfunctions [ 98 ], consistent with a previous clinical trial involving elderly diabetic patients, in which HBOT resulted in improved myocardial diastolic function [ 191 ]. Researchers also examined the effects of HBOT on myocardial function during normal aging.…”
Section: Therapeutic Implications Of Hbot In Aging Interventionsupporting
confidence: 79%
“…Intriguingly, in two independent reports, HBOT respectively showed its ability to attenuate aging markers in the hippocampus of d -galactose (D-gal)-induced aging mice, as demonstrated by decreased number of SA-β-gal positive cells [ 66 ] and reduced expression of key components of the senescence program, such as p16, p21 and p53 [ 71 ]. It has also been shown that HBOT can reduce the number of SA-β-gal positive cells in cardiomyocytes in aging pre-diabetic rats [ 98 ]. In another study, researchers evaluated cellular senescence by lipofuscin, another established biomarker, and found senescent cells cleared from skin after HBOT [ 27 ].…”
Section: The Mechanisms By Which Hbot Intervenes Agingmentioning
confidence: 99%
See 3 more Smart Citations